Gender Differences in the Victim–Offender Relationship for On- and Offline Youth Violence - Semenza, Daniel C. (Journal of interpersonal violence, 2021)
Youth violence affects millions of young people in the United States every day, and violent victimization has significant consequences for mental and physical health, academic performance, and long-term well-being. Forms of youth violence such bullying and teen dating violence (TDV) are often studied separately from one another with disjointed attention paid to on- and offline aggression. Furthermore, gender differences in the victim/offender overlap for these diverse forms of aggression have been understudied. This is notable given research demonstrating that boys and girls engage in diverse forms of aggression as a result of different gendered socialization processes. This study uses a sample of 5,647 middle and high school students in three states to assess gender differences in the victim–offender relationship across on- and offline modalities of bullying and TDV. Descriptive results show significant gender differences for bullying and dating violence victimization and perpetration experiences. Multivariate regression models indicate that the victim–offender relationship varies by the type of aggression and modality in question. Furthermore, gender significantly interacts with certain forms of dating violence and bullying victimization to influence the risk of perpetration. The results underscore the importance of youth violence prevention strategies that account for gender differences across the spectrum of on- and offline peer relationships.